PENGUATAN PERAN KADER KESEHATAN DALAM PENEMUAN KASUS TUBERKULOSIS (TB) BTA POSITIF MELALUI EDUKASI DENGAN PENDEKATAN THEORY OF PLANNED BEHAVIOUR (TPB) - Ni Putu Sumartini (Jurnal Kesehatan Prima, 2014)
Abstract: Undetected TB case makes the patients do not benefit from TB treatment. The low detection rate of TB with positive acid fast bacillus is one of the health problem including in Mataram city by case detection rate is 43,65% in 2011, therefore the role of health cadres in TB case detection need to be strengthened through education using Theory of planned behaviour (TPB) approach. This study aimed to prove the influence of education with TPB approach in strengthening the role of health cadre in TB case detection and increase detection rate of TB with positive acid fast bacillus. Methods: The study design was quasi-experimental with pretest-posttest group design. Samples size of 32 respondents for treatment group and 32 respondents for control group who were meet inclusion criteria. Data were collected using a questionnaires. Statistical analysis used Wilcoxon Sign Rank Test, Mann-Whitney Test and chi-square with a significance level of 5 % (α = 0,05). Result: The result revealed that age, work period and training TB/DOTS of health cadres have a relationship with the role of health cadres in TB case finding based on chi-square test with p value 0,031 for age, p=0,024 for work period and p=0,003 for training of TB/DOTS; education using TPB approach affects the role of health cadres in TB case finding with p=0,001 for health cadres, while increasing case detection rate of TB case with positive acid fast bacillus from 6,42% in 2012 to 8,19%. Discussion: In conclusion, education with TPB approach affects the role of  health cadres in TB case finding and increase detection rate of TB case with positive acid fast bacillus.